Faktor - Faktor yang Berhubungan dengan Derajat Kaparahan Karies di Kecamatan Slawi Kabupaten Tegal Propinsi Jawa Tengah Tahun 1998 - Febrina Setiawati (Faculty of Dentistry, Universitas Indonesia, 2015)
Residence of Slawi Subdistrict, Tegal District Central Java Province have a frequent tea drinking habit with specific characters of high concentrate tea without sugar or a lot of sugar. It is acknowledged that fluor content in tea can prevent dental caries, while sugar, a sucrose type of carbohydrate in the tea is most cariogenic. The subject of the study, regarding the tea drinking habit, is to obtain information about factors correlated to severity of dental caries in residence of the Slawi Subdistrict, Tegal Distric, Central Java Province. The study type is cross sectional with a sample size of 140. The subjects of the study were residents of Slawi Subdistric with age ranging from 18 to 44 years. An interview was conducted to obtain information of tea drinking characteristics. Samples of tea, water and sugar from each subject examined in a laboratory to obtain the information about fluor and and sugar contents in tea. Saliva examination was also conducted to know its buffer capacity and flow rate. Intra oral clinical examination was conducted to obtain DMF-T and plaque scores. Statistical analysis was applied with multiple linear regression methods using SPSS 7.5 and Stata version 4. The result of the study show that caries prevalence of 76.92% in subjects with tea drinking habit without sugar. The subjects had a 2.85 DMF-T score. Meanwhile caries prevalence was 98.15% for subjects with tea drinking habit with sugar. The subjects had a 6.15 DMF-T score. The mean of fluor concentration in all subjects drinking water was 0.11 mg/l, and 5.26% for sugar content. 68.94% of DMF-T score variation concluded in the multiple linear regression model, is showed by the factors in the model.